Education, Labor Market, and Development: A Review of the Trends and Issues in the Philippines for the Past 25 Years - Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2002)
This paper comprehensively reviews the developments in the education and labor markets in the Philippines in the past 25 years. It highlights the trends on how the labor market used educated workers. It also reviews how education has contributed to national development. Furthermore, it summarizes the recommendations of several comprehensive reviews done for the sector in the last decade. Finally, it identifies research areas for the sector.
Keywords: 330; education; labor; human resources; Bildung; Bildungspolitik; Bildungsinvestition; Arbeitsmarkt; Arbeitsnachfrage; Entwicklung; Philippinen